Nasal angiomyolipoma: Report of two cases of an extremely rare entity - Mohammed Abdul Aleem; Ather Fatima; P Kumudachalam; Ramya Priyadarshini (Wolters Kluwer Medknow Publications, 2017)
Nasal angiomyolipoma (AML) are extremely rare tumors and so far <15 cases have been reported in the literature, and this is the first instance that Nasal AML is reported from India. We report two cases of AML arising in the nasal cavity described in 60-year-old male and 50-year-old female patient. Grossly, they were well circumscribed, lobulated masses, and microscopically, they were composed of an intimate mixture of mature fat, smooth muscle cells, and thick-walled varying sized blood vessels. Immunoexpression pattern and histopathology were characteristic. Both the patients had complete resolution of symptoms after endoscopic excision of the tumor.